2020
DOI: 10.1091/mbc.e19-10-0576
|View full text |Cite
|
Sign up to set email alerts
|

Genetically inspired in vitro reconstitution ofSaccharomyces cerevisiaeactin cables from seven purified proteins

Abstract: Yeast actin cables are reconstituted from seven purified proteins, providing a powerful demonstration of how a minimal set of components can self-organize into a micron-scale structure that has many of the same features of actin cables found in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Those studies demonstrated that robust and tunable actin flows are regulated by two main components: the actin turnover rate and the network geometry. In parallel, reconstitution of dynamic networks with a balance between assembly and disassembly mediated by actin polymerization and disassembly by ADF/cofilin (Michelot et al , 2007; Akin & Mullins, 2008; Reymann et al , 2011; Manhart et al , 2019; Pollard et al , 2020) has allowed to better understand the role of the different molecular actors in the establishment of a dynamic steady state. However, those experiments were performed either with cell extracts where precise protein content is unknown or with purified proteins in unlimited volumes (therefore masking some crucial steps existing when a limited amount of component is available).…”
Section: Introductionmentioning
confidence: 99%
“…Those studies demonstrated that robust and tunable actin flows are regulated by two main components: the actin turnover rate and the network geometry. In parallel, reconstitution of dynamic networks with a balance between assembly and disassembly mediated by actin polymerization and disassembly by ADF/cofilin (Michelot et al , 2007; Akin & Mullins, 2008; Reymann et al , 2011; Manhart et al , 2019; Pollard et al , 2020) has allowed to better understand the role of the different molecular actors in the establishment of a dynamic steady state. However, those experiments were performed either with cell extracts where precise protein content is unknown or with purified proteins in unlimited volumes (therefore masking some crucial steps existing when a limited amount of component is available).…”
Section: Introductionmentioning
confidence: 99%
“…Assays can be further modified to use cell extracts that may add the “missing” unknown key factors required to recapitulate cell-like phenomena. For example, TIRF-based assays employing yeast or Xenopus extracts have reconstituted contractile actomyosin rings 37 , mitotic spindles 26 , 38 , components of actin or microtubule assembly 39 , 40 , and even dynamics at the centrosome and kinetochores 36 , 41 , 42 , 43 . Moreover, such systems may pave the way toward artificial cell systems that have lipids or signaling factors present 44 , 45 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Elegant in vitro studies confirm at the level of single actin filaments that tropomyosin excludes other ABPs, such as fimbrin or ADF/cofilin, therefore preventing filaments from disassembly [129,134,148,149]. Interestingly, tropomyosin is not required per se to assemble cables in vitro in the absence of disassembling factors but it becomes necessary to maintain cable assembly in biomimetic assays where treadmilling has been reconstituted [136,150]. Tropomyosins are hence major biochemical regulators that define the identity of actin filaments and regulate the binding of many families of ABPs, thereby leading to the segregation of these proteins to different actin networks.…”
Section: Tropomyosins and The Biogenesis Of New Actin Substratesmentioning
confidence: 99%